The relationship between scores in the Peabody Library Information Test and achievement in library science courses by beginning library science students - Lazarte, Rosario L.; Castillo, Jovito; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1975)
This study attempted to determine the relationship between the Peabody Library Information Test, Form A, College Level and the academic achievement of beginning library science students. The relationship between the scores on the Peabody Library Information Test taken during the second and third week of the first semester by students in Arellano University, Far Eastern University, National Teachers' College, Philippine Normal College, Philippine Women's University, University of Santo Tomas and University of the East and the final grades that these students received after the first semester in a number of library science courses was analyzed. The Pearson "r" was used and these obtained "r's" were tested for significance by using statistic "t". The relationship, then, between scores on the Peabody Library Information Test and the final grades in six subjects are found to be significant beyond .01 level; the relationship between the scores on the Peabody Library Information Test and final grades in two subjects are not significant at the .01 level but are significant at the .05 level. Generally, it can be concluded that a significant relationship exists although when partial correlation was applied, the effect of the second subject taken simultaneously reduced the relationship between scores on the Peabody Library Information Test and the final grades in the first subject.
The predictive value of the test was determined by regression coefficient analysis. To a certain, though limited, extent the test determined the probable achievement of a library science student in library science courses.
This study further tried to determine the reliability of the Peabody Library Information Test by the split-half method. The reliability coefficient thus obtained is .88. When this was stepped up by the Spearman Brown Prophecy Formula, the "r" of the whole test became .94. This proves, therefore, that the test is highly valid and reliable.
Based on the findings of this investigation, the following recommendations are hereby presented.1. Although the Peabody Library Information Test has been found to be valid and reliable for the purposes of the present study, it is suggested that additional validity and reliability testing should be done for at least three more years in the institutions from which the sample came.2. In order to establish a stronger and more extensive value of the Peabody Library Information Test, additional correlation testing should be done with other library science subjects besides those that were used in this study.3. Additional studies on the relationship between the Peabody Library Information Test and academic achievement in library science should also be made with students from other colleges included as samples.4. Since the Peabody Library Information Test has been found to have a significant correlation with library science courses and to some extent has a predictive value, its use as a screening tool for prospective students in library science may be recommended.5. The format and the theoretical constructs of the Peabody Library Information Test may be used as a model for making a standardized test in library science inasmuch as this test has been proven to be valid and reliable for Filipino students.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic achievement; Peabody Library Information Test